The Role of Metaxy in the Political Philosophy of Eric Voegelin - Duraj, Jarosław (Peter Lang US, 2021)
This book is a study of Eric Voegelin (1901-1985) and of the role played by metaxy in his vision of political philosophy. Metaxy, already defined by Plato as the "in-between" matrix of the human condition, is for Voegelin a powerful notion that symbolizes the intermediate state in which man experiences diverse and opposing tensions such as the ones between immanence and transcendence or mortality and immortality. The metaxy constitutes the realm of the divine-human mutual participation (methexis), and its locus resides in human consciousness (nous), there where the divine reality manifests itself as the origin of being. Being the field of intermediation between opposing forces, man has to keep the balance of consciousness in order to differentiate the noetic and pneumatic dimensions and so attune his life to the divine ground of being. This book claims that for Voegelin metaxy shapes the possibility of the philosophical, historical, political and religious orientation in life. Indeed, Voegelin’s approach deserves recognition as an option adequate for addressing the intellectual challenges engendered by modern and postmodern philosophies.

Bioethics : ethics of life - Gomez, Fausto B. (University of Saint Tomas Publishing House, 2021)

A cognitive semantic study of biblical Hebrew: the root šlm for completeness-balance - Leong, Andrew Chin Hei (Studies in semitic languages and linguistics, 2021)
"Semantic studies of the Biblical Hebrew verb "whole" have been influenced by those of its most invoked nominal form "whole". In this volume Andrew Chin Hei Leong shows that the concepts of balance, alliance, and completeness form the basic semantic structure of "whole". Previous studies on "whole" employed either historical or textual methodology, which has been dominant in biblical lexical studies. In addition to these methods, in Leong develops a systematic semantic methodology from Cognitive Semantics and Frame Semantics, to demonstrate that it is balance, rather than completeness, that is the most central concept in holding the semantic network together"--
Keywords: Bible; Hebrew language; Language, style; Semantics; Shlm (The Hebrew root)

Predictive Models for Decision Support in the COVID-19 Crisis - Marques, João Alexandre Lobo; Gois, Francisco Nauber Bernardo; Xavier-Neto, Jose; Fong, Simon James (SpringerBriefs in Applied Sciences and Technology, 2021)
COVID-19 has hit the world unprepared, as the deadliest pandemic of the century. Governments and authorities, as leaders and decision makers fighting the virus, enormously tap into the power of artificial intelligence and its predictive models for urgent decision support. This book showcases a collection of important predictive models that used during the pandemic, and discusses and compares their efficacy and limitations. Readers from both healthcare industries and academia can gain unique insights on how predictive models were designed and applied on epidemic data. Taking COVID19 as a case study and showcasing the lessons learnt, this book will enable readers to be better prepared in the event of virus epidemics or pandemics in the future.

John Henry Newman and the development of doctrine: encountering change, looking for continuity - Morgan, Stephen (The Catholic University of America Press, 2021)
"In focusing on the gestation of "An Essay on the Development of Christian Doctrine" (1845), John Henry Newman's last work as an Anglican and presaging his transition to Catholicism, this book examines how Newman accounted for doctrinal continuity in the face of evidence of change in the history of the church"--

Sacred and the Everyday: Comparative Approaches to Literature, Religious and Secular - Morgan, Stephen (USJ Press, 2021)

Taming randomized controlled trials in education: exploring key claims, issues and debates - Morrison, Keith (Routledge, Taylor & Francis Group, 2021)
"There is a recent surge in the use of randomized controlled trials (RCTs) within education globally, with disproportionate claims being made about what they show, 'what works', and what constitutes the best 'evidence'. Drawing on up-to-date scholarship from across the world, Taming Randomized Controlled Trials in Education critically addresses the increased use of RCTs in education, exploring their benefits, limits and cautions, and ultimately questioning the prominence given to them. While acknowledging that randomized controlled trials do have some place in education, the book nevertheless argues that this place should be limited. Drawing together all arguments for and against RCTs in a comprehensive and easily accessible single volume, the book also adds new perspectives and insights to the conversation; crucially, the book considers the limits of their usefulness and applicability in education, raising a range of largely unexplored concerns about their use. Chapters include discussions on: The impact of complexity theory and chaos theory Design issues and sampling in randomized controlled trials Learning from clinical trials Data analysis in randomized controlled trials Reporting, evaluating and generalizing from randomized controlled trials. Considering key issues in understanding and interrogating research evidence, this book is ideal reading for all students on Research Methods modules, as well as those interested in undertaking and reviewing research in the field of education"--
Keywords: Clinical trials; Education; Educational indicators; Research Data processing; Research Methodolgy

Retrieving the Sense of the Sacred: a Paradigm of Silence in the Liturgy - Wong, Lee Chun (USJ Theses and Dissertations, 2021)
Keywords: Catholic Church; Liturgy Theology; Religious aspects Catholic Church; Silence

Pilgrimage Christian and Secular: a Phenomenological Approach - Yuan, Haojun (USJ Theses and Dissertations, 2021)
In the light of the many kinds of journeys that have been considered pilgrimages, this book uses phenomenology as a method to examine the claim that pilgrimage is a journey to the ‘center’ during which pilgrims seek meaning s for themselves. First, by analyzing a phenomenology of Christian pilgrimage, this work attempts to identify what commonalities, as well as differences, exist between Christian pilgrimage and secular pilgrimage in terms of ‘natural attitude’. Next, by using a phenomenological method, such as transcendental reduction, the distinction between these two types of pilgrimage could be clarified that the happiness sought in Christian pilgrimage is both intentionally spiritual and sustainable, while primarily intellectual or sensory in secular pilgrimage. Lastly, this work seeks to establish whether or not ‘being at leisure’ is the primary element for pilgrims whose aim is to attain an understanding of happiness during a pilgrimage
Keywords: Christian pilgrims and pilgrimages; Phenomenology

The Role of Metaxy in the Political Philosophy of Eric Voegelin - Duraj, Jarosław (Peter Lang, 2021)
This book is a study of Eric Voegelin (1901-1985) and of the role played by metaxy in his vision of political philosophy. Metaxy, already defined by ...

Book of Proceedings of ARTECH 2021 - 10th International Conference on Digital and Interactive Arts (Hybrid Praxis – Art, Sustainability & Technology) - Lopes, Maria Manuela; Lopes, Paulo Bernardino; Araújo, António; Olivero, Lucas Fabian; Marcos, Adérito Fernandes (2021)